Kajian Model Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Keaktifan Dan Hasil Belajar Siswa SMK - Bhayu Handoyo Aji; Suparmin Suparmin; Nurcholish Arifin Handoyono (JURNAL VOKASI DEWANTARA (JVD), 2020)
The purpose of this study is to know the implementation of cooperative learning model type STAD (Student Teams Achievement Division) can improve the activeness and results of learning basic automotive technology vocational school students. This study is a study using the method of literature review. The analysis method used uses qualitative descriptive analysis of journals and research results. Preliminary study results show that students' activeness and learning outcomes in basic automotive technology subjects are low. This is due to the lack of creativity and innovation of teachers applying learning models. Teachers still use lecture methods in learning so that learning is judged to be less effective. The effort that can be made to improve the activeness and learning outcomes of students is to implement a cooperative learning model type STAD. The implementation of stad-type cooperative learning models is considered suitable because in the learning process students work with each other, thus directing students to provide a live learning experience to be active, critical thinking, logical, innovative, and creative. Through cooperative learning models students do not rely too much on teachers, but can increase confidence in their own thinking skills. The implementation of stad-type cooperative learning models will create an interesting learning atmosphere, as well as improve students' understanding of learning so that the learning process runs effectively and the learning results will be satisfactory.